Pandemi COVID-19 dan Prediksi Kebangkrutan: Apakah Kondisi Keuangan Sebelum 2020 Berperan? - Mikhael Andre Kurniawan; Kerinea Estetika Hariadi; Widya Oktarina Sulistyaningrum; Ari Budi Kristanto (Universitas Kristen Maranatha, 2021)
This study aims to analyze the impact of the COVID-19 pandemic on the prediction of company bankruptcy in Indonesia, with financial conditions before 2020 (cash position and debt position) as moderating variables. Relationship between variables was tested using a logistic regression analysis model test with a moderation model. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange. A total of 169 samples were obtained using purposive sampling with the criteria: listed on the IDX in 2020, had financial information for 2019-2020, and the company reported information disclosure regarding the impact of the pandemic. The results show that companies with a high impact of the COVID-19 pandemic will be more predicted to go bankrupt, furthermore the cash position and debt ratio in 2019 have no moderating effect. Keywords: Bankruptcy, Liquidity, Leverage, Pandemic COVID-19